PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Hasannudin Hasannudin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
The purpose of this study is to determine and analyze the effect of profitability on dividend policy; to determine and analyze the effect of dividend policy on firm value; and to determine and analyze the effect of profitability on firm value. The analytical method employs regression analysis using SPSS as a statistical testing tool, as well as path analysis to examine the factors influencing firm value. The results indicate that profitability has a positive effect on dividend policy. The higher the level of a company’s profitability, the greater its ability to implement its dividend policy. Dividend policy has a positive effect on firm value. Consistent dividend distribution can enhance shareholder welfare and provide a positive signal to investors, thereby increasing firm value. Profitability also has a positive effect on firm value. The higher the company’s profitability, the higher the firm value. Dividend policy is able to mediate the relationship between profitability & firm value. High profitability increases the company’s ability to distribute div idends to shareholders, ultimately contributes to enhancing firm value.